Dairy consumption and risk of type-2 diabetes: the untold story - Sai Krishna Gudi (Korean Society of Pediatric Endocrinology, 2021)
The role of dairy products in human health has been extensively studied for decades; however, evidence regarding dairy consumption and risk of type 2 diabetes (T2D) remains controversial and uncertain. Furthermore, study results are misinterpreted to a remarkable extent. The aim of this review is to critically appraise the association between intake of dairy foods and risk of T2D. A thorough search was conducted using electronic databases of PubMed, Scopus, and Web of Science. Related studies that addressed this research question between 2004 to 2019 were considered. Although most of the existing evidence suggests a beneficial role of dairy consumption on risk of T2D, only low-fat dairy foods and yogurt have shown a significant and consistent role, while other dairy products showed no association with prevention of T2D. Researchers, readers, and the public should maintain caution when reporting and interpreting findings and consider aspects such as heterogeneity, generalizability, and clinical and statistical significance.